HIGH-LIFT BEHAVIOUR OF HALF-MODELS AT FLIGHT REYNOLDS NUMBERS - PIOTR DOERFFER; OSKAR SZULC (TASK Quarterly, 2006)
A peniche is designed to offset a half-span aircraft model from the wind tunnel wall boundary layer. This strategy of model mounting results in large influence on the measured aerodynamic coefficients, compared with full-span data. The negative influence is especially important in high-lift conditions leading to incorrect maximum lift behaviour.